Parkinson Disease: An Overview for the Management Techniques Via Physical Therapy - Alameer, Abdulaziz Ali Hasan; Alhuraysi , Muhammed Ali Mofareh; Alhazmi, Mohammad Ismail; Al-Ghamdi , Wael Abdulghani Mohammed; Alshehri, Saeed Abdullah Aziz; Maashi, Sultan Mohammed; Al-Ghashmari, Khalid Hassan Ali (Journal of Ecohumanism, 2024)
Background: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor symptoms such as bradykinesia, resting tremor, and rigidity, as well as non-motor symptoms including sleep disturbances, mood disorders, and autonomic dysfunction. It affects approximately 1% of individuals aged 60 and older, with both genetic and environmental factors contributing to its etiology. The pathophysiology involves the degeneration of dopaminergic neurons in the substantia nigra and the accumulation of alpha-synuclein in Lewy bodies. Aim: This article provides an overview of PD, focusing on its clinical presentation, pathophysiology, and management strategies, with an emphasis on the role of physical therapy in improving functional outcomes and quality of life. Methods: The review synthesizes current literature on PD, including its epidemiology, etiology, histopathology, and clinical features. It also examines evidence-based management techniques, particularly the integration of physical therapy into multidisciplinary care. Results: PD is diagnosed clinically, with physical therapy playing a critical role in addressing motor and non-motor symptoms. Key interventions include gait and balance training, strength and flexibility exercises, and task-specific activities. Physical therapy has been shown to improve mobility, reduce fall risk, and enhance overall well-being, though long-term adherence remains a challenge. Non-motor symptoms, such as depression and autonomic dysfunction, require a holistic approach involving pharmacological and non-pharmacological strategies. Conclusion: PD is a multifaceted disorder requiring comprehensive management. Physical therapy is a vital component of care, offering significant benefits in improving motor function and quality of life. However, sustained outcomes depend on ongoing support and adherence to exercise programs. A multidisciplinary approach, including physical therapists, physicians, and other healthcare professionals, is essential for optimizing patient outcomes